Composite coating material of PCB milling cutter and preparation method of composite coating material

By depositing Cr bonding layer, TiAlN transition layer and NbCrAlY alloy layer on PCB milling cutter, combined with gas plasma cleaning and pulse negative bias control, the problem of excess hardness but insufficient toughness in high-speed cutting is solved. It achieves higher wear resistance and service life, reduces friction coefficient and hardness, and improves processing accuracy and stability.

CN119220939AActive Publication Date: 2024-12-31SHENZHEN HANS RUILI TIDE PRECISION COATING CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411424153.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2024-12-31
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

The existing PCB milling cutter coating materials have problems such as excess hardness, insufficient toughness, and insufficient bonding between layers during high-speed cutting, resulting in reduced machining accuracy and shortened tool life.

Method used

Using a multi-step coating deposition process, the Cr bonding layer, TiAlN transition layer and NbCrAlY alloy layer are deposited successively, combining gas plasma cleaning and pulse negative bias control to form a composite coating structure to improve the adhesion between the coating and the substrate and the whole. performance.

Benefits of technology

It significantly improves the wear resistance and service life of the coating, reduces the friction coefficient and hardness, improves processing accuracy and stability, extends the tool replacement cycle, and improves the thermal stability of the coating through the ice-water cooling step.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a composite coating material of a PCB milling cutter and a preparation method of the composite coating material, and belongs to the technical field of novel functional materials.A coating structure which is well designed comprises a Cr bonding layer, a TiAlN transition layer and an NbCrAlY alloy layer, the high bonding force between a coating and a base body is achieved, and the service life of the coating is prolonged. And meanwhile, the coating shows excellent mechanical properties and a relatively low friction coefficient. The preparation method of the coating comprises the steps of precisely controlled cleaning, sputtering deposition and cooling, so that the uniformity and stability of the coating are ensured. The coating material provided by the invention adopts an optimized element ratio, especially a specific combination of niobium, chromium, aluminum and rare earth element yttrium, so that the high-temperature oxidation resistance and wear resistance of the coating are further improved. Compared with the prior art, the surface composite hardness of the obtained coating under the load of 10 g reaches up to 59 GPa, the friction coefficient of the coating matched with GCr15 is as low as 0.21, and the coating is suitable for the field of PCB machining requiring high precision and high efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of novel functional materials, and in particular to a composite coating material for a PCB milling cutter and a preparation method thereof. Background Art

[0002] With the rapid development of the electronics industry, the requirements for PCB processing accuracy and efficiency are getting higher and higher. As a key tool in PCB processing, the performance of the milling cutter directly affects the processing quality. However, traditional milling cutters are prone to wear and damage during high-speed cutting, resulting in reduced processing accuracy and shortened tool life. In order to improve the performance of milling cutters, the industry generally uses coating technology to improve the hardness, wear resistance and chemical stability of milling cutters.

[0003] Existing coating technologies mainly include single material coatings and simple composite coatings. Although these coatings have improved the performance of milling cutters to a certain extent, they still have certain limitations. For example, single material coatings often have more hardness than toughness, while simple composite coatings may have limited performance improvement due to insufficient interlayer bonding or mismatched material properties.

[0004] In the prior art, China's invention patent CN103436841B discloses a yttrium-modified chromium aluminum carbonitride / silicon nitride nanocomposite coating and its deposition method, the purpose of which is to form a nanocomposite structure of nanocrystalline chromium aluminum carbonitride implanted in amorphous silicon nitride by nanocomposite design of chromium aluminum carbonitride and silicon nitride, improve the hardness of the coating while taking into account the toughness of the coating and the bonding strength between the coating and the substrate, and introduce rare earth element Y to further improve the mechanical properties and high-temperature oxidation resistance of the coating, so as to obtain a nanocomposite coating for high-speed steel, carbide tools, and molds with strong bonding force, high hardness, good toughness, low friction coefficient, and outstanding thermal stability. The coating includes a chromium aluminum yttrium bonding layer, a chromium aluminum yttrium nitride transition layer, and a nanocomposite layer; the obtained coating has a film / substrate bonding strength of 40~90N, a surface composite hardness of 40~65GPa under a load of 10g, and a friction coefficient of 0.2~0.5 with a GCr15 pair. However, the composite coating prepared by the invention has poor bonding strength, hardness and wear resistance. Summary of the invention

[0005] In view of the shortcomings of the existing technology, this paper aims to provide a new type of composite coating material, which can not only significantly improve the hardness and wear resistance of the milling cutter, but also maintain sufficient toughness and thermal stability, so as to meet the needs of high-speed and high-precision PCB processing.

[0006] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions: A method for preparing a composite coating material for a PCB milling cutter is as follows: Step 1, select a PCB milling cutter as a substrate, and perform degreasing, rust removal, organic solution cleaning, water rinsing and drying treatments on the substrate; Step 2: Place the cleaned and dried substrate into a coating furnace; evacuate the furnace and maintain the temperature at 240-280°C; perform gas plasma cleaning by introducing He and H2; Step 3, turn off the gas ion source, adjust the pulse negative bias, and adjust the He and H2 partial pressures to 0.1~0.3Pa and 0.05~0.1Pa; start the arc ion plating Cr target, the arc source current is 80~95A, and perform bombardment sputtering cleaning for 5~10 minutes; Step 4, depositing a Cr bonding layer, adjusting the pulse negative bias frequency to 80-90kHz, the peak value to 200-240V, the duty cycle to 80-90%, the He and H2 partial pressures to 0.3-0.4Pa and 0.1-0.2Pa, and the Cr target arc source current to 80-95A; the deposition time to 3-5 minutes, and the thickness to 0.1-0.5 microns; Step 5, depositing a TiAlN transition layer on the bonding layer, keeping the pulse negative bias voltage unchanged, turning off He, introducing N2, with a partial pressure of 0.3-0.4 Pa; using a TiAl alloy target, the deposition time is 2-4 minutes, and the thickness is 0.1-0.5 microns; Step 6, keep the pulse negative bias voltage and the partial pressure of N2 and H2 unchanged, the Cr target current unchanged, turn on the ion plating NbCrAlY alloy target, and increase the current linearly from 40~60A to 80~100A within 8~12min, the deposition time is 5~15min, and the thickness is 1~1.5μm; Step 7, keep the pulse negative bias voltage unchanged, the N2 and H2 partial pressures unchanged, turn off the ion plating Ti target, keep the ion plating NbCrAlY alloy target arc source current 80~100A, deposit the nano two-phase composite layer for 70~100min, and the thickness is 3~5 microns; after the coating is stopped, use ice water to cool for 40~60 minutes and take out the workpiece.

[0007] The PCB milling cutter has a blade length of 20-30 mm and a blade diameter of 0.8-3.175 mm.

[0008] In step 2, the vacuum is evacuated to 1×10 ⁻3 ~2×10 ⁻3 Pa.

[0009] In step 2, the set partial pressures of the gas plasma cleaning are 0.2-0.3 Pa and 0.1-0.2 Pa, respectively, the ion source current is 10-15 A, a pulsed negative bias is applied, the frequency is 80-90 kHz, the peak value is 300-350 V, the duty cycle is 80-90%, and the cleaning time is 20-40 minutes.

[0010] In step 3, the pulse negative bias voltage is adjusted to a frequency of 80-90 kHz, a peak value of 1100-1300 V, and a duty cycle of 30-40%.

[0011] The atomic percentage of Ti in the TiAl alloy target is 50-70%, and the atomic percentage of Cr is 35-55%.

[0012] In the NbCrAlY alloy target, the atomic percentage of Nb is 35-45%, the atomic percentage of Cr is 20-30%, the atomic percentage of Al is 25-35%, and the atomic percentage of Y is 1-10%.

[0013] The organic solution is one of acetone and isopropanol.

[0014] In the present invention, the functions of each substance are as follows: As the carrier of the coating, the PCB milling cutter substrate needs to have certain mechanical strength and thermal stability to ensure the adhesion of the coating and the cutting performance of the milling cutter.

[0015] The steps of degreasing, rust removal and acetone cleaning are to remove oil, rust and other contaminants on the surface of the substrate and ensure good bonding between the coating and the substrate.

[0016] Gas plasma cleaning uses a mixture of helium and hydrogen for plasma cleaning to remove oxides and other adsorbents on the substrate surface, providing a clean surface for coating deposition.

[0017] Pulsed Negative Bias Applying a pulsed negative bias during the sputtering process helps control the sputtering efficiency and energy and optimize the quality and structure of the coating.

[0018] The Cr target is used to deposit the Cr bonding layer. The chromium layer as a bonding layer can improve the bonding strength between the coating and the substrate and serve as the base layer for subsequent coatings.

[0019] TiAl alloy target is used to deposit TiAlN transition layer. The titanium and aluminum elements in the titanium aluminum target can form a hard TiAlN phase to improve the hardness and wear resistance of the coating.

[0020] NbCrAlY alloy target is used to deposit nano-duplex composite layer. This alloy target contains niobium, chromium, aluminum and rare earth element yttrium. The specific combination of these elements helps to form a composite coating with excellent properties, improving the hardness, wear resistance and chemical stability of the coating.

[0021] After coating, rapid cooling with ice water helps reduce the thermal stress of the coating and improve the density and stability of the coating.

[0022] Careful selection and control of each substance and step is to ensure high performance of the final coating, thereby improving the overall performance and service life of the PCB milling cutter.

[0023] Compared with the prior art, it has the following beneficial effects: 1) The present invention forms a composite coating structure by sequentially depositing a Cr bonding layer, a TiAlN transition layer and a NbCrAlY alloy layer on a PCB milling cutter substrate. This structure not only enhances the adhesion between the coating and the substrate, but also significantly improves the wear resistance and service life of the coating through the optimized combination of different material layers.

[0024] 2) The coating materials and process parameters used in the present invention are carefully selected and adjusted, so that the final composite coating exhibits a lower friction coefficient and higher hardness. These performance improvements help improve the stability and processing accuracy of the milling cutter during high-speed cutting, while also reducing tool wear and extending the tool replacement cycle.

[0025] 3) The coating preparation method of the present invention adopts a series of coating steps, including gas plasma cleaning, pulsed negative bias control, and sputtering deposition of different target materials. The combination of these steps ensures the uniformity and density of the coating. In addition, the introduction of the ice water cooling step improves the thermal stability of the coating. The design of the entire process improves production efficiency and reduces production costs. DETAILED DESCRIPTION

[0026] The remaining raw materials in the examples and comparative examples of the present invention are all commercially available products.

[0027] The design idea of ​​the present invention is to adopt a multi-step coating deposition process to achieve the preparation of a composite coating material with excellent performance on a PCB milling cutter substrate. First, a strict substrate pretreatment step is performed to ensure good bonding between the coating and the substrate. Then, impurities on the substrate surface are removed by gas plasma cleaning technology to provide a clean surface for coating deposition. Next, a Cr bonding layer, a TiAlN transition layer, and a nano-duplex composite layer of a NbCrAlY alloy target are sequentially deposited by precisely controlled sputtering parameters, and each layer is optimized for a specific function to enhance the overall performance of the coating. Finally, rapid heat treatment is achieved by ice water cooling to improve the hardness and stability of the coating. The entire preparation process focuses on the integrity of the coating structure and the precise control of the composition, ensuring the high hardness, strong bonding force, and low friction coefficient of the coating, thereby significantly improving the service life and processing performance of the PCB milling cutter.

[0028] Example 1 A method for preparing a composite coating material for a PCB milling cutter is as follows: Step 1: Select a PCB milling cutter as the substrate, with a blade length of 27.500 mm and a blade diameter of 1.815 mm; degrease, derust, clean with acetone, rinse with water, and dry the substrate; Step 2, load the cleaned and dried substrate into the coating furnace; evacuate to 1.8×10⁻³Pa, maintain the temperature at 260°C; perform gas plasma cleaning, introduce He and H2, set the partial pressures to 0.25Pa and 0.15Pa respectively, the ion source current to 12A, apply pulsed negative bias, frequency to 86kHz, peak value to 320V, duty cycle to 88%, and cleaning time to 30 minutes; Step 3, turn off the gas ion source, adjust the pulse negative bias to a frequency of 86kHz, a peak value of 1200V, a duty cycle of 35%, and adjust the He and H2 partial pressures to 0.2Pa and 0.08Pa; start the arc ion plating of the Cr target, the arc source current is 90A, and perform bombardment sputtering cleaning for 8 minutes; Step 4, depositing a Cr bonding layer, adjusting the pulse negative bias frequency to 86kHz, the peak value to 220V, the duty cycle to 88%, the He and H2 partial pressures to 0.35Pa and 0.15Pa, and the Cr target arc source current to 90A; the deposition time to 4 minutes, the thickness to 0.3 microns; Step 5, depositing a TiAlN transition layer on the bonding layer, keeping the pulse negative bias voltage unchanged, turning off He, introducing N2, with a partial pressure of 0.35 Pa; using a TiAl alloy target, the deposition time is 3 minutes, and the thickness is 0.3 microns; Step 6, keeping the pulse negative bias voltage and the partial pressures of N2 and H2 unchanged, the Cr target current unchanged, turning on the ion plating NbCrAlY alloy target, the current linearly increased from 50A to 90A within 10min, the deposition time was 10min, and the thickness was 1.2 microns; Step 7, keep the pulse negative bias voltage unchanged, the N2 and H2 partial pressures unchanged, turn off the ion plating Ti target, keep the ion plating NbCrAlY alloy target arc source current at 90A, deposit the nano two-phase composite layer for 80 minutes with a thickness of 4 microns; after the coating is stopped, use ice water to cool for 50 minutes and take out the workpiece.

[0029] The atomic percentage of Ti in the TiAl alloy target is 60%, and the atomic percentage of Cr is 40%; The atomic percentage of Nb in the NbCrAlY alloy target is 40%, the atomic percentage of Cr is 25%, the atomic percentage of Al is 30%, and the atomic percentage of Y is 5%.

[0030] Example 2 A method for preparing a composite coating material for a PCB milling cutter is as follows: Step 1: Select a PCB milling cutter as the substrate, with a blade length of 27.500 mm and a blade diameter of 1.815 mm; degrease, derust, clean with acetone, rinse with water, and dry the substrate; Step 2, load the cleaned and dried substrate into the coating furnace; evacuate to 1.8×10⁻³Pa, maintain the temperature at 260°C; perform gas plasma cleaning, introduce He and H2, set the partial pressures to 0.25Pa and 0.15Pa respectively, the ion source current to 12A, apply pulsed negative bias, frequency to 86kHz, peak value to 320V, duty cycle to 88%, and cleaning time to 30 minutes; Step 3, turn off the gas ion source, adjust the pulse negative bias to a frequency of 86kHz, a peak value of 1200V, a duty cycle of 35%, and adjust the He and H2 partial pressures to 0.2Pa and 0.08Pa; start the arc ion plating of the Cr target, the arc source current is 90A, and perform bombardment sputtering cleaning for 8 minutes; Step 4, depositing a Cr bonding layer, adjusting the pulse negative bias frequency to 86kHz, the peak value to 220V, the duty cycle to 88%, the He and H2 partial pressures to 0.35Pa and 0.15Pa, and the Cr target arc source current to 90A; the deposition time to 4 minutes, the thickness to 0.3 microns; Step 5, depositing a TiAlN transition layer on the bonding layer, keeping the pulse negative bias voltage unchanged, turning off He, introducing N2, with a partial pressure of 0.35 Pa; using a TiAl alloy target, the deposition time is 3 minutes, and the thickness is 0.3 microns; Step 6, keeping the pulse negative bias voltage and the partial pressures of N2 and H2 unchanged, the Cr target current unchanged, turning on the ion plating NbCrAlY alloy target, the current linearly increased from 50A to 90A within 10min, the deposition time was 10min, and the thickness was 1.2 microns; Step 7, keep the pulse negative bias voltage unchanged, the N2 and H2 partial pressures unchanged, turn off the ion plating Ti target, keep the ion plating NbCrAlY alloy target arc source current at 90A, deposit the nano two-phase composite layer for 80 minutes with a thickness of 4 microns; after the coating is stopped, use ice water to cool for 50 minutes and take out the workpiece.

[0031] The atomic percentage of Ti in the TiAl alloy target is 60%, and the atomic percentage of Cr is 40%; The atomic percentage of Nb in the NbCrAlY alloy target is 30%, the atomic percentage of Cr is 30%, the atomic percentage of Al is 35%, and the atomic percentage of Y is 5%.

[0032] Example 3 A method for preparing a composite coating material for a PCB milling cutter is as follows: Step 1: Select a PCB milling cutter as the substrate, with a blade length of 27.500 mm and a blade diameter of 1.815 mm; degrease, derust, clean with acetone, rinse with water, and dry the substrate; Step 2, load the cleaned and dried substrate into the coating furnace; evacuate to 1.8×10⁻³Pa, maintain the temperature at 260°C; perform gas plasma cleaning, introduce He and H2, set the partial pressures to 0.25Pa and 0.15Pa respectively, the ion source current to 12A, apply pulsed negative bias, frequency to 86kHz, peak value to 320V, duty cycle to 88%, and cleaning time to 30 minutes; Step 3, turn off the gas ion source, adjust the pulse negative bias to a frequency of 86kHz, a peak value of 1200V, a duty cycle of 35%, and adjust the He and H2 partial pressures to 0.2Pa and 0.08Pa; start the arc ion plating of the Cr target, the arc source current is 90A, and perform bombardment sputtering cleaning for 8 minutes; Step 4, depositing a Cr bonding layer, adjusting the pulse negative bias frequency to 86kHz, the peak value to 220V, the duty cycle to 88%, the He and H2 partial pressures to 0.35Pa and 0.15Pa, and the Cr target arc source current to 90A; the deposition time to 4 minutes, the thickness to 0.3 microns; Step 5, depositing a TiAlN transition layer on the bonding layer, keeping the pulse negative bias voltage unchanged, turning off He, introducing N2, with a partial pressure of 0.35 Pa; using a TiAl alloy target, the deposition time is 3 minutes, and the thickness is 0.3 microns; Step 6, keeping the pulse negative bias voltage and the partial pressures of N2 and H2 unchanged, the Cr target current unchanged, turning on the ion plating NbCrAlY alloy target, the current linearly increased from 50A to 90A within 10min, the deposition time was 10min, and the thickness was 1.2 microns; Step 7, keep the pulse negative bias voltage unchanged, the N2 and H2 partial pressures unchanged, turn off the ion plating Ti target, keep the ion plating NbCrAlY alloy target arc source current at 90A, deposit the nano two-phase composite layer for 80 minutes with a thickness of 4 microns; after the coating is stopped, use ice water to cool for 50 minutes and take out the workpiece.

[0033] The atomic percentage of Ti in the TiAl alloy target is 60%, and the atomic percentage of Cr is 40%; The atomic percentage of Nb in the NbCrAlY alloy target is 50%, the atomic percentage of Cr is 20%, the atomic percentage of Al is 25%, and the atomic percentage of Y is 5%.

[0034] Example 4 A method for preparing a composite coating material for a PCB milling cutter is as follows: Step 1: Select a PCB milling cutter as the substrate, with a blade length of 27.500 mm and a blade diameter of 1.815 mm; degrease, derust, clean with acetone, rinse with water, and dry the substrate; Step 2, load the cleaned and dried substrate into the coating furnace; evacuate to 1.8×10⁻³Pa, maintain the temperature at 260°C; perform gas plasma cleaning, introduce He and H2, set the partial pressures to 0.25Pa and 0.15Pa respectively, the ion source current to 12A, apply pulsed negative bias, frequency to 86kHz, peak value to 320V, duty cycle to 88%, and cleaning time to 30 minutes; Step 3, turn off the gas ion source, adjust the pulse negative bias to a frequency of 86kHz, a peak value of 1200V, a duty cycle of 35%, and adjust the He and H2 partial pressures to 0.2Pa and 0.08Pa; start the arc ion plating of the Cr target, the arc source current is 90A, and perform bombardment sputtering cleaning for 8 minutes; Step 4, depositing a Cr bonding layer, adjusting the pulse negative bias frequency to 86kHz, the peak value to 220V, the duty cycle to 88%, the He and H2 partial pressures to 0.35Pa and 0.15Pa, and the Cr target arc source current to 90A; the deposition time to 4 minutes, the thickness to 0.3 microns; Step 5, depositing an AlCrN transition layer on the bonding layer, keeping the pulse negative bias voltage unchanged, turning off He, introducing N2, with a partial pressure of 0.35 Pa; using an AlCr alloy target, the deposition time is 3 minutes, and the thickness is 0.3 microns; Step 6, keeping the pulse negative bias voltage and the partial pressures of N2 and H2 unchanged, the Cr target current unchanged, turning on the ion plating NbCrAlY alloy target, the current linearly increased from 50A to 90A within 10min, the deposition time was 10min, and the thickness was 1.2 microns; Step 7, keep the pulse negative bias voltage unchanged, the N2 and H2 partial pressures unchanged, turn off the ion plating Ti target, keep the ion plating NbCrAlY alloy target arc source current at 90A, deposit the nano two-phase composite layer for 80 minutes with a thickness of 4 microns; after the coating is stopped, use ice water to cool for 50 minutes and take out the workpiece.

[0035] The AlCr alloy target has an Al atomic percentage of 60% and a Cr atomic percentage of 40%; The atomic percentage content of the NbCrAlY alloy target is the same as that in Example 1.

[0036] Example 5 A method for preparing a composite coating material for a PCB milling cutter is as follows: Step 1: Select a PCB milling cutter as the substrate, with a blade length of 27.500 mm and a blade diameter of 1.815 mm; degrease, derust, clean with acetone, rinse with water, and dry the substrate; Step 2, load the cleaned and dried substrate into the coating furnace; evacuate to 1.8×10⁻³Pa, maintain the temperature at 260°C; perform gas plasma cleaning, introduce He and H2, set the partial pressures to 0.25Pa and 0.15Pa respectively, the ion source current to 12A, apply pulsed negative bias, frequency to 86kHz, peak value to 320V, duty cycle to 88%, and cleaning time to 30 minutes; Step 3, turn off the gas ion source, adjust the pulse negative bias to a frequency of 86kHz, a peak value of 1200V, a duty cycle of 35%, and adjust the He and H2 partial pressures to 0.2Pa and 0.08Pa; start the arc ion plating of the Cr target, the arc source current is 90A, and perform bombardment sputtering cleaning for 8 minutes; Step 4, depositing a Cr bonding layer, adjusting the pulse negative bias frequency to 86kHz, the peak value to 220V, the duty cycle to 88%, the He and H2 partial pressures to 0.35Pa and 0.15Pa, and the Cr target arc source current to 90A; the deposition time to 4 minutes, the thickness to 0.3 microns; Step 5, depositing a CrAlYN transition layer on the bonding layer, keeping the pulse negative bias voltage unchanged, turning off He, introducing N2, with a partial pressure of 0.35 Pa; using a CrAlY alloy target, the deposition time is 3 minutes, and the thickness is 0.3 microns; Step 6, keeping the pulse negative bias voltage and the partial pressures of N2 and H2 unchanged, the Cr target current unchanged, turning on the ion plating NbCrAlY alloy target, the current linearly increased from 50A to 90A within 10min, the deposition time was 10min, and the thickness was 1.2 microns; Step 7, keep the pulse negative bias voltage unchanged, the N2 and H2 partial pressures unchanged, turn off the ion plating Ti target, keep the ion plating NbCrAlY alloy target arc source current at 90A, deposit the nano two-phase composite layer for 80 minutes with a thickness of 4 microns; after the coating is stopped, use ice water to cool for 50 minutes and take out the workpiece.

[0037] The atomic percentage of Cr in the CrAlY alloy target is 55%, the atomic percentage of Al is 40%, and the atomic percentage of Y is 5%; The atomic percentage content of the NbCrAlY alloy target is the same as that in Example 1.

[0038] Example 6 A method for preparing a composite coating material for a PCB milling cutter is as follows: Step 1: Select a PCB milling cutter as the substrate, with a blade length of 27.500 mm and a blade diameter of 1.815 mm; degrease, derust, clean with acetone, rinse with water, and dry the substrate; Step 2, load the cleaned and dried substrate into the coating furnace; evacuate to 1.8×10⁻³Pa, maintain the temperature at 260°C; perform gas plasma cleaning, introduce He and H2, set the partial pressures to 0.25Pa and 0.15Pa respectively, the ion source current to 12A, apply pulsed negative bias, frequency to 86kHz, peak value to 320V, duty cycle to 88%, and cleaning time to 30 minutes; Step 3, turn off the gas ion source, adjust the pulse negative bias to a frequency of 86kHz, a peak value of 1200V, a duty cycle of 35%, and adjust the He and H2 partial pressures to 0.2Pa and 0.08Pa; start the arc ion plating of the Cr target, the arc source current is 90A, and perform bombardment sputtering cleaning for 8 minutes; Step 4, depositing a Cr bonding layer, adjusting the pulse negative bias frequency to 86kHz, the peak value to 220V, the duty cycle to 88%, the He and H2 partial pressures to 0.35Pa and 0.15Pa, and the Cr target arc source current to 90A; the deposition time to 4 minutes, the thickness to 0.3 microns; Step 5, depositing a TiAlN transition layer on the bonding layer, keeping the pulse negative bias voltage unchanged, turning off He, introducing N2, with a partial pressure of 0.35 Pa; using a TiAl alloy target, the deposition time is 3 minutes, and the thickness is 0.3 microns; Step 6, keeping the pulse negative bias voltage and the partial pressures of N2 and H2 unchanged, the Cr target current unchanged, turning on the ion plating NbCoSiY alloy target, the current linearly increased from 50A to 90A within 10min, the deposition time 10min, the thickness 1.2μm; Step 7, keep the pulse negative bias voltage unchanged, the N2 and H2 partial pressures unchanged, turn off the ion plating Ti target, keep the ion plating NbCoSiY alloy target arc source current at 90A, deposit the nano two-phase composite layer for 80 minutes with a thickness of 4 microns; after stopping the coating, use ice water to cool for 50 minutes and take out the workpiece.

[0039] The atomic percentage content of the TiAl alloy target is the same as that in Example 1.

[0040] The atomic percentage of Nb in the NbCoSiY alloy target is 40%, the atomic percentage of Co is 25%, the atomic percentage of Si is 30%, and the atomic percentage of Y is 5%.

[0041] Example 7 A method for preparing a composite coating material for a PCB milling cutter is as follows: Step 1: Select a PCB milling cutter as the substrate, with a blade length of 27.500 mm and a blade diameter of 1.815 mm; degrease, derust, clean with acetone, rinse with water, and dry the substrate; Step 2, load the cleaned and dried substrate into the coating furnace; evacuate to 1.8×10⁻³Pa, maintain the temperature at 260°C; perform gas plasma cleaning, introduce He and H2, set the partial pressures to 0.25Pa and 0.15Pa respectively, the ion source current to 12A, apply pulsed negative bias, frequency to 86kHz, peak value to 320V, duty cycle to 88%, and cleaning time to 30 minutes; Step 3, turn off the gas ion source, adjust the pulse negative bias to a frequency of 86kHz, a peak value of 1200V, a duty cycle of 35%, and adjust the He and H2 partial pressures to 0.2Pa and 0.08Pa; start the arc ion plating of the Cr target, the arc source current is 90A, and perform bombardment sputtering cleaning for 8 minutes; Step 4, depositing a Cr bonding layer, adjusting the pulse negative bias frequency to 86kHz, the peak value to 220V, the duty cycle to 88%, the He and H2 partial pressures to 0.35Pa and 0.15Pa, and the Cr target arc source current to 90A; the deposition time to 4 minutes, the thickness to 0.3 microns; Step 5, depositing a TiAlN transition layer on the bonding layer, keeping the pulse negative bias voltage unchanged, turning off He, introducing N2, with a partial pressure of 0.35 Pa; using a TiAl alloy target, the deposition time is 3 minutes, and the thickness is 0.3 microns; Step 6, keeping the pulse negative bias voltage and the partial pressures of N2 and H2 unchanged, the Cr target current unchanged, turning on the ion plating NbAlTiSi alloy target, the current linearly increased from 50A to 90A within 10min, the deposition time 10min, the thickness 1.2μm; Step 7, keep the pulse negative bias voltage unchanged, the N2 and H2 partial pressures unchanged, turn off the ion plating Ti target, keep the ion plating NbAlTiSi alloy target arc source current at 90A, deposit the nano two-phase composite layer for 80 minutes with a thickness of 4 microns; after the coating is stopped, use ice water to cool for 50 minutes and take out the workpiece.

[0042] The atomic percentage content of the TiAl alloy target is the same as that in Example 1.

[0043] The atomic percentage of Nb in the NbAlTiSi alloy target is 40%, the atomic percentage of Al is 25%, the atomic percentage of Ti is 30%, and the atomic percentage of Si is 5%.

[0044] Comparative Example 1 A method for preparing a composite coating material for a PCB milling cutter is as follows: Step 1: Select a PCB milling cutter as the substrate, with a blade length of 27.500 mm and a blade diameter of 1.815 mm; degrease, derust, clean with acetone, rinse with water, and dry the substrate; Step 2, load the cleaned and dried substrate into the coating furnace; evacuate to 1.8×10⁻³Pa, maintain the temperature at 260°C; perform gas plasma cleaning, introduce He and H2, set the partial pressures to 0.25Pa and 0.15Pa respectively, the ion source current to 12A, apply pulsed negative bias, frequency to 86kHz, peak value to 320V, duty cycle to 88%, and cleaning time to 30 minutes; Step 3, turn off the gas ion source, adjust the pulse negative bias to a frequency of 86kHz, a peak value of 1200V, a duty cycle of 35%, and adjust the He and H2 partial pressures to 0.2Pa and 0.08Pa; start the arc ion plating of the Cr target, the arc source current is 90A, and perform bombardment sputtering cleaning for 8 minutes; Step 4, depositing a Cr bonding layer, adjusting the pulse negative bias frequency to 86kHz, the peak value to 220V, the duty cycle to 88%, the He and H2 partial pressures to 0.35Pa and 0.15Pa, and the Cr target arc source current to 90A; the deposition time to 4 minutes, the thickness to 0.3 microns; Step 5, depositing a TiAlN transition layer on the bonding layer, keeping the pulse negative bias voltage unchanged, turning off He, introducing N2, with a partial pressure of 0.35 Pa; using a TiAl alloy target, the deposition time is 3 minutes, and the thickness is 0.3 microns; Step 6: Keep the pulse negative bias voltage and the partial pressures of N2 and H2 unchanged, the Cr target current unchanged, turn on the ion plating NbCrAlY alloy target, increase the current linearly from 50A to 90A within 10 minutes, the deposition time is 10 minutes, and the thickness is 1.2 microns; after the coating is stopped, use ice water to cool for 50 minutes and take out the workpiece.

[0045] The atomic percentage content of the TiAl alloy target is the same as that in Example 1.

[0046] The atomic percentage content of the NbCrAlY alloy target is the same as that in Example 1.

[0047] Comparative Example 2 A method for preparing a composite coating material for a PCB milling cutter is as follows: Step 1: Select a PCB milling cutter as the substrate, with a blade length of 27.500 mm and a blade diameter of 1.815 mm; degrease, derust, clean with acetone, rinse with water, and dry the substrate; Step 2, load the cleaned and dried substrate into the coating furnace; evacuate to 1.8×10⁻³Pa, maintain the temperature at 260°C; perform gas plasma cleaning, introduce He and H2, set the partial pressures to 0.25Pa and 0.15Pa respectively, the ion source current to 12A, apply pulsed negative bias, frequency to 86kHz, peak value to 320V, duty cycle to 88%, and cleaning time to 30 minutes; Step 3, turn off the gas ion source, adjust the pulse negative bias to a frequency of 86kHz, a peak value of 1200V, a duty cycle of 35%, and adjust the He and H2 partial pressures to 0.2Pa and 0.08Pa; start the arc ion plating of the Cr target, the arc source current is 90A, and perform bombardment sputtering cleaning for 8 minutes; Step 4, depositing a Cr bonding layer, adjusting the pulse negative bias frequency to 86kHz, the peak value to 220V, the duty cycle to 88%, the He and H2 partial pressures to 0.35Pa and 0.15Pa, and the Cr target arc source current to 90A; the deposition time to 4 minutes, the thickness to 0.3 microns; Step 5, deposit a TiAlN transition layer on the bonding layer, keep the pulse negative bias voltage unchanged, turn off He, and introduce N2 with a partial pressure of 0.35Pa; use a TiAl alloy target, the deposition time is 3 minutes, and the thickness is 0.3 microns; after the coating is stopped, use ice water to cool for 50 minutes and take out the workpiece.

[0048] The atomic percentage content of the TiAl alloy target is the same as that in Example 1.

[0049] Comparative Example 3 A method for preparing a composite coating material for a PCB milling cutter is as follows: Step 1: Select a PCB milling cutter as the substrate, with a blade length of 27.500 mm and a blade diameter of 1.815 mm; degrease, derust, clean with acetone, rinse with water, and dry the substrate; Step 2, load the cleaned and dried substrate into the coating furnace; evacuate to 1.8×10⁻³Pa, maintain the temperature at 260°C; perform gas plasma cleaning, introduce He and H2, set the partial pressures to 0.25Pa and 0.15Pa respectively, the ion source current to 12A, apply pulsed negative bias, frequency to 86kHz, peak value to 320V, duty cycle to 88%, and cleaning time to 30 minutes; Step 3, turn off the gas ion source, adjust the pulse negative bias to a frequency of 86kHz, a peak value of 1200V, a duty cycle of 35%, and adjust the He and H2 partial pressures to 0.2Pa and 0.08Pa; start the arc ion plating of the Cr target, the arc source current is 90A, and perform bombardment sputtering cleaning for 8 minutes; Step 4, deposit a Cr bonding layer, adjust the pulse negative bias frequency to 86kHz, peak value to 220V, duty cycle to 88%, He and H2 partial pressures to 0.35Pa and 0.15Pa, and Cr target arc source current to 90A; deposition time to 4 minutes, thickness to 0.3 micron; after stopping the coating, cool with ice water for 50 minutes and take out the workpiece.

[0050] Comparative Example 4 A method for preparing a composite coating material for a PCB milling cutter is as follows: Step 1: Select a PCB milling cutter as the substrate, with a blade length of 27.500 mm and a blade diameter of 1.815 mm; degrease, derust, clean with acetone, rinse with water, and dry the substrate; Step 2, load the cleaned and dried substrate into the coating furnace; evacuate to 1.8×10⁻³Pa, maintain the temperature at 260°C; perform gas plasma cleaning, introduce He and H2, set the partial pressures to 0.25Pa and 0.15Pa respectively, the ion source current to 12A, apply pulsed negative bias, frequency to 86kHz, peak value to 320V, duty cycle to 88%, and cleaning time to 30 minutes; Step 3, turn off the gas ion source, adjust the pulse negative bias to a frequency of 86kHz, a peak of 1200V, a duty cycle of 35%, and adjust the He and H2 partial pressures to 0.2Pa and 0.08Pa; start the arc ion plating of the Cr target, the arc source current is 90A, and perform bombardment sputtering cleaning for 8 minutes; remove the workpiece.

[0051] Test Example 1 Friction coefficient test The friction coefficient of the coating and the GCr15 pair was measured by HT-1000 friction and wear testing machine. Each group was tested three times and the average value was taken. The test results are shown in Table 1.

[0052] Table 1 Experimental protocol Friction coefficient Example 1 0.21 Example 2 0.23 Example 3 0.24 Example 4 0.26 Example 5 0.27 Example 6 0.25 Example 7 0.27 Comparative Example 1 0.31 Comparative Example 2 0.34 Comparative Example 3 0.37 Comparative Example 4 0.45 Test Example 2 Wear resistance test The coating hardness was measured with an MH-5 microhardness tester under a load of 10 g. Each group was tested three times and the average value was taken. The test results are shown in Table 2.

[0053] Table 2 Experimental protocol Hardness (GPa) Example 1 59 Example 2 54 Example 3 53 Example 4 51 Example 5 52 Example 6 49 Example 7 47 Comparative Example 1 45 Comparative Example 2 41 Comparative Example 3 39 Comparative Example 4 32 It can be seen from test examples 1 and 2 that the composite coating material obtained in Example 1 of the present invention has the smallest friction coefficient and the highest hardness.

[0054] The NbCrAlY alloy target in Example 1 exhibits a lower friction coefficient and higher hardness, mainly due to its specific element ratio and coating characteristics. The 40% niobium (Nb) content optimizes the hardness and wear resistance of the coating, while the ratio of chromium (Cr) and aluminum (Al) is adjusted to 25% and 30%, which may help to form a more stable compound and enhance the coating performance. At the same time, the addition of 5% of the rare earth element yttrium (Y) may improve the high temperature performance and wear resistance of the coating. In terms of microstructure, possible fine grains and uniformly distributed second phases further improve the overall performance of the coating. The phase composition of the coating, which may contain more body-centered cubic phases, and optimized preparation processes, such as sputtering conditions and deposition rates, also provide guarantees for obtaining lower friction coefficients and higher hardness. In addition, the coating of Example 1 may form a denser and more stable oxide layer during the friction process, which helps to reduce the friction coefficient and improve wear resistance. The combined effect of these factors makes the coating of Example 1 superior to Examples 2 and 3 in performance.

[0055] The TiAl alloy target (60%Ti, 40%Al) exhibited a lower friction coefficient and higher hardness in Example 1. The possible reason is that the structural characteristics of the TiAl alloy itself and the influence of the preparation process on the coating performance. TiAl alloy has high hardness and good thermal stability, which enables it to provide a lower friction coefficient and higher wear resistance when forming a coating. In the TiAl alloy target, the ratio of Ti and Al has a significant effect on the structure and properties of the coating. The ratio of 60%Ti and 40%Al may form a better microstructure, thereby improving the hardness and wear resistance of the coating. In addition, during the sputtering process of the TiAl alloy target, Ti and Al elements exist as a single phase, in which Ti atomic particles are embedded in the Al matrix. This structure is conducive to the production of more metal ions during the sputtering process, thereby improving the deposition rate and quality of the coating. The ratio of different elements in the AlCr alloy target and the CrAlY alloy target may lead to different microstructures and phase compositions, affecting the hardness and friction coefficient of the coating. During the deposition process of the coating, the Ti and Al elements in the TiAl alloy target are transformed from a single phase structure into an ion flow state with a certain energy. With the participation of the reaction gas, they combine with N atoms, thereby improving the hardness and bonding strength of the coating.

[0056] The NbCrAlY alloy target in Example 1 exhibits a lower friction coefficient and higher hardness than the NbCoSiY alloy target in Example 6 and the NbAlTiSi alloy target in Example 7. In Example 1, the content of chromium (Cr) is higher than that of cobalt (Co) and titanium (Ti) in Examples 6 and 7. Chromium is an element with high hardness and stable chemical properties, which helps to improve the hardness and wear resistance of the coating, thereby reducing the friction coefficient. The aluminum (Al) content in the NbCrAlY alloy is relatively high, and aluminum can generally improve the hardness and high temperature resistance of the material. At the same time, the combination of aluminum with niobium (Nb) and chromium may form a compound with good comprehensive properties, which helps the coating to remain stable during friction and reduce wear. Different alloy target materials may lead to differences in the microstructure of the coating, such as grain size, phase composition, etc. The coating in Example 1 may have finer and more uniform grains and better phase distribution, which help to improve the hardness and wear resistance of the coating.

[0057] In Example 1, the coating structure consists of a bonding layer, a transition layer and a nano dual-phase composite layer. This multi-layer structure design helps to improve the overall performance of the coating. The bonding layer provides a firm bond with the substrate, the transition layer helps to distribute stress and reduce coating defects, and the composite layer provides excellent wear resistance and hardness.

Claims

1. A method for preparing a composite coating material for a PCB milling cutter, characterized in that: Here’s how: Step 1, select a PCB milling cutter as a substrate, and perform degreasing, rust removal, organic solution cleaning, water rinsing and drying treatments on the substrate; Step 2: Place the cleaned and dried substrate into a coating furnace; evacuate the furnace and maintain the temperature at 240-280°C; perform gas plasma cleaning by introducing He and H2; Step 3, turn off the gas ion source, adjust the pulse negative bias, and adjust the He and H2 partial pressures to 0.1~0.3Pa and 0.05~0.1Pa; start the arc ion plating Cr target, the arc source current is 80~95A, and perform bombardment sputtering cleaning for 5~10 minutes; Step 4, depositing a Cr bonding layer, adjusting the pulse negative bias frequency to 80-90kHz, the peak value to 200-240V, the duty cycle to 80-90%, the He and H2 partial pressures to 0.3-0.4Pa and 0.1-0.2Pa, and the Cr target arc source current to 80-95A; the deposition time to 3-5 minutes, and the thickness to 0.1-0.5 microns; Step 5, depositing a TiAlN transition layer on the bonding layer, keeping the pulse negative bias voltage unchanged, turning off He, introducing N2, with a partial pressure of 0.3-0.4 Pa; using a TiAl alloy target, the deposition time is 2-4 minutes, and the thickness is 0.1-0.5 microns; Step 6, keep the pulse negative bias voltage and the partial pressure of N2 and H2 unchanged, the Cr target current unchanged, turn on the ion plating NbCrAlY alloy target, and increase the current linearly from 40~60A to 80~100A within 8~12min, the deposition time is 5~15min, and the thickness is 1~1.5μm; Step 7, keep the pulse negative bias voltage unchanged, the N2 and H2 partial pressures unchanged, turn off the ion plating Ti target, keep the ion plating NbCrAlY alloy target arc source current 80~100A, deposit the nano two-phase composite layer for 70~100min, and the thickness is 3~5 microns; after the coating is stopped, use ice water to cool for 40~60 minutes and take out the workpiece.

2. The method for preparing the composite coating material for a PCB milling cutter according to claim 1, characterized in that: The PCB milling cutter has a blade length of 20-30 mm and a blade diameter of 0.8-3.175 mm.

3. The method for preparing the composite coating material for a PCB milling cutter according to claim 1, characterized in that: In step 2, the vacuum is evacuated to 1×10 ⁻3 ~2×10 ⁻3 Pa.

4. The method for preparing the composite coating material for a PCB milling cutter according to claim 1, characterized in that: In step 2, the set partial pressures of the gas plasma cleaning are 0.2-0.3 Pa and 0.1-0.2 Pa, respectively, the ion source current is 10-15 A, a pulsed negative bias is applied, the frequency is 80-90 kHz, the peak value is 300-350 V, the duty cycle is 80-90%, and the cleaning time is 20-40 minutes.

5. The method for preparing the composite coating material for a PCB milling cutter according to claim 1, characterized in that: In step 3, the pulse negative bias voltage is adjusted to a frequency of 80-90 kHz, a peak value of 1100-1300 V, and a duty cycle of 30-40%.

6. The method for preparing the composite coating material for a PCB milling cutter according to claim 1, characterized in that: The atomic percentage of Ti in the TiAl alloy target is 50-70%, and the atomic percentage of Cr is 35-55%.

7. The method for preparing the composite coating material for a PCB milling cutter according to claim 1, characterized in that: In the NbCrAlY alloy target, the atomic percentage of Nb is 35-45%, the atomic percentage of Cr is 20-30%, the atomic percentage of Al is 25-35%, and the atomic percentage of Y is 1-10%.

8. The method for preparing the composite coating material for a PCB milling cutter according to claim 1, characterized in that: The organic solution is one of acetone and isopropanol.

9. A composite coating material for a PCB milling cutter, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Direct liquid injection system and method for forming multi-component dielectric films

    CN101040371A

  • Method for lowering interfacial element interdiffusion between high-temperature alloy and protective coating

    CN104357782A

  • Surface coating equipment of neodymium iron boron permanent magnet device and surface coating method

    CN111218655A

  • Cutting tool having hard coating layer with excellent wear resistance and toughness

    CN118302560A

  • Method of depositing a MCrAIY bond coating

    EP1260608A1